Recontextualization: Schema-Based Pre-Reading Activity - Milagros Villas (Bandar Lampung University (UBL), 2013)
The study Recontextualizationof ”Veronika Decides to Die”: Schema-Based Pre-Reading Activity is aimed at preparing the pre-reading activities as a means to draw out the students’ concerns in the real world. With the growing incidences in the country of young people committing suicide, Literature classes can serve as an effective venue for the students to reflect about their lives and learn from other people from different cultures and periods of time that man can provide solutions to problems. The methodology involved preparing a lesson with the following pre-reading activities: a) listened to a tribute made by a classmate to someone who committed suicide, b) listened to the song “Why?” by Rascal Flatts to draw reactions about committing suicide, c) made students take an adapted Anger Management Test, wherein the focus was not to determine the interpretation of the results but to make the students reflect about how they handle difficult situations, d) grouped the class into 5 (Group A-E) to discuss about the questions given, d) reported to class on the discussion made among the group members.The questions given for discussion were as follows: 1) How do the students manage their negative emotions – anger, anxiety, depression or worse, emptiness? 2) What would be the possible reasons which drive young people to commit suicide? 3) What would you do if you were like Veronika who survived death after committing suicide and was given the chance to live 5 more days? The findings were that they have their parents to cling to when they have problems; some believe they can manage or that they will seek the support from their peers or friends. The reasons that they cited as those why young people commit suicide are as follows: the pressure they feel from their parent’s expectations from them; losing a loved on and pressure borne from the desire to succeed in life so they can help their families. As to how they would spend the remaining days after having been rescued from death, the students considered making amends to those they wronged, staying with their loved ones and rekindling relationships.The answers of the students were not really new but having drawn out responses from them about the realities in young peoples’ lives was significantly important. The term ‘recontextualization’ is not simply introduced and utilized as a strategy but as a means to awaken the recesses of the students’ consciousness about what may possibly happen to them should they fall prey to the pressures around them.